2019
DOI: 10.1177/0300060519875898
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenge for giant left retroperitoneal accessory spleen: a case report

Abstract: An accessory spleen refers to single or multiple splenic tissues that appear outside the normal spleen position and have structures and functions similar to those of a normal spleen. We herein present a rare case of a 31-year-old woman who was hospitalized because of a 14-year history of sudden left upper abdominal pain after running. Abdominal computed tomography suggested a large soft tissue mass at the left renal hilum surrounded by several enlarged lymph nodes, which was totally different from computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…In our case, imaging ndings of the retroperitoneal mass led to misdiagnose of the accessory spleen. They showed that the principal supply artery of the lesion was native of the left common iliac artery instead of the splenic artery according to the literature (11). On the other hand, the size of the mass in our case was too much larger than reported in the literature, and its enhancement scanning pattern was different from the main spleen.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our case, imaging ndings of the retroperitoneal mass led to misdiagnose of the accessory spleen. They showed that the principal supply artery of the lesion was native of the left common iliac artery instead of the splenic artery according to the literature (11). On the other hand, the size of the mass in our case was too much larger than reported in the literature, and its enhancement scanning pattern was different from the main spleen.…”
Section: Discussioncontrasting
confidence: 55%
“…Nowadays, Only nuclear medicine imaging can con rm the diagnosis using Technetium-99m heatdamaged red blood cell scintigraphy or Tc-99m heat-damaged autologous red blood cell SPECT-CT which are the key mean to differentiate accessory splenic tissue (3,(11)(12)(13). This modality concludes approximately the site of the accessory spleen, but is only performed when there is a high suspicious index (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] At the fifth week of embryonic development, an accessory spleen may form if the embryo spleen bud is not fully fused or if a single cell is separated from the body of the spleen. [ 5 ] An accessory spleen is a congenital defect, [ 6 ] 1 to 3 pieces, about 1.0 cm in diameter, normally located in the left upper abdomen, around the normal spleen. Abnormally enlarged accessory spleen may be found after splenectomy with or without hypersplenism.…”
Section: Introductionmentioning
confidence: 99%
“…The spleen is derived from mesenchymal cells of the dorsal mesentery,and appears approximately at the sixth week of embryologic life [ 1 , 2 ]. The spleen is located between the 9th and 11th left ribs in abdominal cavity, between the gastric bottom and the left diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…With a weight of approximately 200 g, it represents the largest lymphoid organ in the body [ 3 ]. At the fifth week of embryonic development, an accessory spleen may form if the embryo spleen bud is not fully fused or its single cell is separated from the body of the spleen, which is a congenital defect [ 2 , 4 ]. Accessory spleen is common and typical in most imaging manifestations.…”
Section: Introductionmentioning
confidence: 99%